2022
DOI: 10.1039/d1fo03854k
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates enterotoxigenicEscherichia coliK88-induced damage by regulating SIRT-1 signaling in intestinal porcine epithelial cells

Abstract: This study found that resveratrol pretreatment attenuated the porcine intestinal epithelial cell damage caused by enterotoxigenic Escherichia coli (ETEC) K88 in vitro and the protective effects of resveratrol were associated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
(99 reference statements)
1
5
0
Order By: Relevance
“…Moreover, Sirt 1 and Parkin have been proven to play vital roles in mitophagy, which is involved in the immune response caused by pathogenic bacteria. 41 In the current study, the expression levels of the Sirt 1 and Parkin genes in the jejunal mucosa of broilers in the B. licheniformis treatment group were enhanced significantly compared with those in the CP-challenged group, indicating that B. licheniformis may mitigate the intestinal immune response by regulating the mitophagy response mediated by Sirt 1 signalling. However, the specific mechanism requires further research.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Moreover, Sirt 1 and Parkin have been proven to play vital roles in mitophagy, which is involved in the immune response caused by pathogenic bacteria. 41 In the current study, the expression levels of the Sirt 1 and Parkin genes in the jejunal mucosa of broilers in the B. licheniformis treatment group were enhanced significantly compared with those in the CP-challenged group, indicating that B. licheniformis may mitigate the intestinal immune response by regulating the mitophagy response mediated by Sirt 1 signalling. However, the specific mechanism requires further research.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, treatment with 500 mg kg −1 B. licheniformis significantly down‐regulated the expression of TLR4 , NF‐κB , NLRP3 , Caspase 1 , TNF‐α , IL‐1β and IL‐18 in the jejunal mucosa of CP ‐challenged broilers, suggesting that B. licheniformis may improve the intestinal immune response by regulating the activation of the TLR4/NF‐κB signalling pathway and NLRP3 inflammasome. Moreover, Sirt 1 and Parkin have been proven to play vital roles in mitophagy, which is involved in the immune response caused by pathogenic bacteria 41 . In the current study, the expression levels of the Sirt 1 and Parkin genes in the jejunal mucosa of broilers in the B. licheniformis treatment group were enhanced significantly compared with those in the CP ‐challenged group, indicating that B. licheniformis may mitigate the intestinal immune response by regulating the mitophagy response mediated by Sirt 1 signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al [ 14 ] showed that dietary resveratrol improved the IgG content in weaned piglets challenged with Salmonella typhimurium and E. coli . In vitro resveratrol alleviated E. coli K88 infection-induced damage, including decreased cell viability, reduced tight junctions, mitochondrial dysfunction, and autophagy in the porcine intestinal epithelial cell by activating SIRT1 signaling [ 132 ]. For viruses, resveratrol treatment relieved the inflammation response by inhibiting the TNF-α production and inhibited rotavirus infection by enhancing the IFN-γ content and CD4 + /CD8 + ratio, decreasing the diarrhea index [ 103 ].…”
Section: Application Of Resveratrol In Swine Productionmentioning
confidence: 99%
“…Interestingly, AQP3 silencing inhibited cell viability and autophagy in gastric cancer cells while AQP3 overexpression activated autophagy via Krüpper like factor 5 as confirmed by chromatin immunoprecipitation and dual luciferase reporter assays ( Dai et al, 2023 ). Moreover, increasing data has indicated that ETEC infection caused significant autophagy in porcine intestinal epithelial cells ( Tang et al, 2014 ; Xia et al, 2019 ; Luo et al, 2022 ). In addition to ETEC, a recent study showed that PEDV induced autophagy in Vero CCL81 cells ( Ren et al, 2022 ).…”
Section: Role and Regulation Of Aqp3 In Intestinal Oxidative Stress A...mentioning
confidence: 99%